Utility and Cost-effectiveness of Motivational Messaging to Increase Survey Response in Physicians: A Randomized Controlled Trial. Issue 1 (February 2018) - Chan, Randolph C. H.; Mak, Winnie W. S.; Pang, Ingrid H. Y.; Wong, Samuel Y. S.; Tang, Wai Kwong; Lau, Joseph T. F.; Woo, Jean; Lee, Diana T. F.; Cheung, Fanny M.
The present study examined whether, when, and how motivational messaging can boost the response rate of postal surveys for physicians based on Higgin's regulatory focus theory, accounting for its cost-effectiveness. A three-arm, blinded, randomized controlled design was used. A total of 3, 270 doctors were randomly selected from the registration list. Results showed that motivational messaging was effective in boosting response rate among younger physicians at relatively low cost when the messages were sent during the delivery of generic invitation letter and questionnaire. However, message framing had no significant impact on postal surveys' response rate. Future postal surveys can consider using motivational messaging to maximize survey participation in physician population without incurring much extra cost.